PUBLIC RELATIONS ACTIVITIES AS A MANAGEMENT FUNCTION IN DECISION MAKING IN THE BUREAU OF PUBLIC RELATIONS AND PROTOCOL REGIONAL SECRETARIAT OF BANTEN PROVINCE - Ipat Ramadani; Eli Apud Saepudin; Shifa Fadilah; Rossa Amelia Putri; Nahara Merlita; Ratu Al Viola Gunawan (Pt. Anagata Sembagi Education, 2024)
The Public Relations and Protocol Bureau is an important unit in an organization that has a strategic role in supporting organizational performance. This research aims to analyze the strategic role of the Public Relations and Protocol Bureau. This research uses a case study method by collecting data through interviews, observation, and documentation. The results showed that the Public Relations and Protocol Bureau has an important role in supporting organizational performance through: Building and maintaining good relationships with internal and external publics. Disseminating information and publications about the organization Managing the organization's image and reputation Handling communication crises Planning and organizing official organizational events Welcoming and accompanying VIP guests Organizing procedures and protocol in official events Providing services and hospitality to guests. Decision-making is an important process in management that determines the direction and success of the organization. The success of decision-making is greatly influenced by the effective application of management functions.